Del conocimiento antropológico y de su patrimonialización - García García, José Luis (Política y Sociedad, 2007)
The first publications out of the Spanish Ethnographic Survey of the Section of Moral and Political Sciences from the Ateneo of Madrid about customs on birth, marriage and death are one hundred years old. The survey, just in the midway between folklore and anthropology, became an heritage utilized to set boundaries and scientific identities which still have a truly effect today. For this reason, following the development of writtings out of the survey, this essay reflects on the value of the patrimonialization of scientific knowledge, and it shows up that this is a necessary condition for the progress of social sciences beyond some particular rethoric usages.